ORGANISASI PEMBELAJARAN PADA PONDOK PESANTREN DALAM di ERA GLOBAL - Sidiq, Umar (IAIN Ponorogo, 2014)
Abstract; in the growth of Islamic Boarding School, Islamic Boarding School leadership shall no longer apply single leadership pattern. Islamic Boarding School organization developed in the legal form of institution. Islamic Boarding School Organizational toward impersonal without lessening role of kyai as highest leader, with leadership like that, Islamic Boarding School become one of the modern education institute. Islamic Boarding School leadership shall no longer apply single leadership pattern but in the form of legal form of institution. With leadership like that, Islamic Boarding School become one of the modern education institute. Learning Organization is appliance to develop quality institution or organization. Every organizational member require to develop its ability continually for future. Applying of study organization conducted because organization have core value to improve strategic ability for the process of action repair, improve knowledge and skilled its member. Thereby, Continuity of Islamic Boarding School exist finally shall no longer depend on someone as single leader a kyai, but have rounded into a working team. This matter represent good growth for continuity of Islamic Boarding School.Â Ù ÙØ®Øµ: Ø·Ø¨ÙØ§ ÙÙÙ ÙÙ Ø§ÙÙ Ø¹Ø§ÙØ¯ (Ø§ÙØ¨Ø³Ø§ÙØªØ±ÙÙ) ÙØ¥Ù Ø§ÙØ±Ø¦Ø§Ø³Ø© ÙÙÙØ§ ÙÙØ³Øª Ø±Ø¦Ø§Ø³Ø© ÙØ§ØØ¯Ø©. ØªÙØ¸ÙÙ Ù ÙØ¸Ù Ø© Ø§ÙÙ Ø¹ÙØ¯ ÙÙ Ø´ÙÙ Ø§ÙÙ Ø¤Ø³Ø³Ø© Ø ÙØ§ØªØ¬Ù Ø¥ÙÙ Ø§ÙØ±Ø¦Ø§Ø³Ø© Ø§ÙØ¬Ù Ø§Ø¹ÙØ©Â ÙÙÙ Ø¯ÙÙ Ø£Ù ÙÙÙÙ Ø¯ÙØ± ÙÙØ§ÙÙ ÙÙÙ ÙØ§ÙØ±Ø¦ÙØ³ Ø§ÙØ£ÙÙ ÙÙÙØ ÙØ¨ÙØ°Ø§ ÙØµØ¨Ø Ø§ÙÙ Ø¹ÙØ¯ Ù Ø¤Ø³Ø³Ø© ØªØ±Ø¨ÙÙØ© Ù ØªÙØ¯ÙÙ Ø©. Ù Â Learning organizationÂ Â ÙÙ Ø§ÙÙØ³ÙÙØ© ÙØ¨ÙØ§Ø¡ Ø§ÙÙ ÙØ¸Ù Ø© Ø£Ù Ø§ÙÙ Ø¤Ø³Ø³Ø© Ø§ÙÙ ØªÙØ¯Ù Ø©. ÙÙÙ Ù Ù Ø£Ø¹Ø¶Ø§Ø¡ ÙØ°Ù Ø§ÙÙ ÙØ¸Ù Ø© ÙØ§Ø¨Ø¯ Ø£Ù ØªÙÙ ÙÙ ÙÙØ§Ø¡Ø§ØªÙ ÙØ£Ø¬Ù Ø§ÙØ¥ØµÙØ§Ø ÙÙ Ø§ÙÙ Ø³ØªÙØ¨Ù. ÙÙØ·Ø¨Ù ØªÙØ³ÙÙ Ø§ÙØªØ¹ÙÙÙ ÙØ£Ù Ø§ÙÙ ÙØ¸Ù Ø© ÙÙØ§ Ø§ÙÙÙÙ Ø© ÙØªÙÙ ÙØ© Ø§ÙÙÙØ§Ø¡Ø§Øª Ø§ÙØ§Ø³ØªÙØ±Ø§ØªÙØ¬ÙØ© ÙØ¹Ù ÙÙØ© Ø¥ØµÙØ§Ø Ø§ÙØ¹Ù ÙØ ÙØªØ±ÙÙØ© Ø§ÙÙ Ø¹ÙÙÙ Ø§Øª ÙØ§ÙÙÙØ§Ø¡Ø§Øª ÙÙÙ Ø£Ø¹Ø¶Ø§Ø¡ Ø§ÙÙ ÙØ¸Ù Ø©. Ø¨ÙØ°Ø§ ÙØ§ ÙÙÙÙ ÙØ¬ÙØ¯ Ø§ÙÙ Ø¹ÙØ¯ Ù Ø¹ÙÙ Ø¨ÙØ¬ÙØ¯ Ø§ÙØ±Ø¦ÙØ³ Ø§ÙÙØÙØ¯ (ÙÙØ§ÙÙ) ÙÙÙÙ Ø£ØµØ¨Ø ÙØ±ÙØ© Ø§ÙØ¹Ù Ù. ÙÙØ°Ø§ ÙØ§ÙØ¹ Ø¬Ù ÙÙ ÙÙ ÙÙØ¹ ÙØ¨ÙØ§Ø¡ Ø§ÙÙ Ø¹ÙØ¯ ÙÙ Ø§ÙÙ Ø³ØªÙØ¨Ù.Keyword: Pembelajaran, organisasi, pesantren dan era global.